Regulatory approach for the approval of Artificial intelligence/ Machine language (AI/ML) Based Software as medical devices (SaMD) (International Journal of Research in Pharmaceutical Sciences and Technology, 2021)
Artificial Intelligence and Machine Language (AI/ML)-Based medical technologies has the potential to change the medical care by determining new and significant experience from the huge measure of information produced during the conveyance of medical care each day.The capacity for AI/ML programming to gain from certifiable criticism (preparing) and improve its presentation (variation) makes these advancements particularly arranged among programming as a clinical gadget (SaMD) and a quickly extending territory of innovative work. Our vision is that with fittingly customized administrative oversight, AI/ML-based SaMD will convey protected and powerful programming usefulness that improves the nature of care that patients get. Different types of medical devices and various documentation procedures for the approval of the AI/ML based SaMD was discussed and the modifications or the updates regulatory approach to the SaMD were clearly mentioned for the easy approval considering the IMDRF, GMLP, TPLC and FD&C regulations. The future trend and the current approved SaMd were discussed.